The Effect of Storytelling Method on Children’s Cognitive Development at the Age of 5–6 Years - Nur Fatwa Khusnul Khatima; Andi Agusniatih; Hesti Putri Setianingsih; Shofiyanti Nur Zuama; João Lima (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Cognitive ability is one of the essential aspects of early childhood development that must be stimulated through approaches aligned with the children’s developmental stages. This study aims to determine the effect of the storytelling method on the cognitive abilities of children aged 5–6 years. The research employed a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The study involved 14 children from Group B as research subjects. Data were collected through observation, interviews, and documentation, using observation sheets, assessment rubrics, and interview guidelines as instruments. The data were analyzed descriptively and inferentially using a paired sample t-test. The results revealed a significant improvement in the aspects of retelling stories, answering questions, and identifying story settings and characters after the implementation of the storytelling method. This improvement was reflected by an increase in the “Very Well Developed” category and a notable decrease in the “Not Yet Developed” category. The t-test results showed a significance value of < 0.05, indicating a significant effect of the storytelling method on children’s cognitive abilities. These findings confirm that the storytelling method is an effective learning approach to actively, enjoyably, and meaningfully stimulate children’s cognitive development in the context of early childhood education.